Benign Paroxysmal Positional Vertigo: comparison of two recent international guidelines - Silva,André Luís dos Santos (2011)
Benign Paroxysmal Positional Vertigo (BPPV) is characterized by vertigo, lasting for a few seconds and usually managed by head positioning maneuvers. To educate clinicians concerning the state-of-the art knowledge about its management, the international societies developed guidelines. AIM: the aim of this paper is to discuss, in a practical fashion, the current options available to manage BPPV. METHOD: Study design: non-systematic review. This study reviews two recent guidelines regarding the evaluation and treatment of BPPV. The first one was published by the American Academy of Otolaryngology Head and Neck surgery (AAO-HNS) and the other by the American Academy of Neurology (AAN). The similarities were presented in different tables. RESULTS: Those guidelines presented differences regarding methods. Only the AAO-HNS guidelines recommend the Dix-Hallpike test for the diagnosis of BPPV. Only canalith repositioning maneuver, Semont maneuver and vestibular rehabilitation had showed some benefit and were recommended as good treatment options. CONCLUSIONS: Both guidelines fulfilled all the aspects required for clinicians to diagnosed and manage BPPV; only the AAO-HNS's guidelines were more comprehensive and of better quality.